2022
DOI: 10.1007/s12126-022-09509-2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Canadian Model of Aging in Place on Community Dwelling Older Adults’ Experience of Physical Distancing during the COVID-19 Pandemic

Abstract: Naturally occurring retirement communities (NORCs) are unplanned communities with a high proportion of residents aged 65 years and older. Oasis is a Canadian aging in place model that combines health and supportive community services for adults aged 65 years and older within NORCs. The aims of this study were to explore how physical distancing restrictions during the COVID-19 pandemic impacted older adults living in a NORC (Oasis members) and to investigate whether Oasis served as a context for social connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…On the other hand, we engage with the literature that studies how digital technologies contribute to alleviating older people's exclusion, isolation, and unwanted loneliness (Beneito-Montagut et al 2023), especially during the pandemic caused by the circulation of the SARS-CoV-2 virus. There has been a significant increase in the number of studies on how digital technologies have helped to mitigate the impact of lockdowns and restrictions on older people (MacLeod et al 2021;Sixsmith et al 2022;Todd et al 2022;Garcia Diaz et al 2023;Zhang et al 2023). Most of these studies concentrate on examining the access, adoption, and use of technologies, as well as the mitigating role of digital "connectedness" (Scarfe et al 2022;Beardmore et al 2023;Garnett et al 2023), mainly from an assistive and health-centric standpoint (Armitage and Nellums 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…On the other hand, we engage with the literature that studies how digital technologies contribute to alleviating older people's exclusion, isolation, and unwanted loneliness (Beneito-Montagut et al 2023), especially during the pandemic caused by the circulation of the SARS-CoV-2 virus. There has been a significant increase in the number of studies on how digital technologies have helped to mitigate the impact of lockdowns and restrictions on older people (MacLeod et al 2021;Sixsmith et al 2022;Todd et al 2022;Garcia Diaz et al 2023;Zhang et al 2023). Most of these studies concentrate on examining the access, adoption, and use of technologies, as well as the mitigating role of digital "connectedness" (Scarfe et al 2022;Beardmore et al 2023;Garnett et al 2023), mainly from an assistive and health-centric standpoint (Armitage and Nellums 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Their research confirmed that one of the groups most at risk of the effects of quarantine were the elderly (60+). Garcia Diaz et al [30] found that face-to-face interactions and support from family, friends, a healthcare provider, and the community alleviated the influence of social distancing restrictions at the time of the COVID-19 pandemic. The deterioration of the well-being of these support groups has had a negative impact on the well-being of older people during the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research identifies variation in altered place engagements and implications for health and wellbeing in early stages of the COVID-19 pandemic, particularly among the oldest old, those living alone, and individuals with chronic health conditions ( Bailey et al, 2021 ; Chen 2021 ; Finlay et al, 2023a , b ; Ottoni et al, 2022 ; Garcia Diaz et al, 2023 ; Xie et al, 2021 ). Less is known about longer-term changes to older adults’ third place engagement and how these changes might vary by broader sociodemographic and geographic characteristics ( Cannon et al, 2023 ; Bustamante et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%